Design and Analysis of Modified-Proportional Fair Scheduler for LTE Femtocell Networks - Ismail, M. K.; A. M. Isa, A.; Johal, M. S.; Ahmad, M. R.; M. Zin, M. S. I.; M. Isa, M. S. M. Isa; Nornikman, H.; M. Mahyuddin, M. F. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Nowadays, Long Term Evolution-Advanced (LTEA) is well known as a cellular network that can support very high data rates in diverse traffic conditions. One way of achieving it is through packet scheduling which is the key scheme of Radio Resource Management (RRM) for LTE-A traffic processing that is functioning to allocate resources for both frequency and time dimensions. The main contribution of this paper is the design of a new scheduling scheme and its performance is compared with the Proportional Fair (PF) and Round Robin (RR) downlink schedulers for LTE-A by utilizing LTE-A Downlink System Level Simulator in femto cell for indoor coverage extension. The proposed new scheduling algorithm, namely the Modified-PF scheduler divides a single sub-frame into multiple time slots and allocates the resource block (RB) to the targeted User Equipment (UE) in all time slots for each sub-frame based on the instantaneous Channel Quality Indicator (CQI) feedback received from UEs. Simulation results show that the Modified-PF scheduler provides the best performance in terms of throughput and spectral efficiency. The Modified-PF scheduler provides a better compromise between the throughput and spectral efficiency. This shows that the newly proposed scheme improves the LTE output performances while at the same time maintains minimal required fairness among the UEs.